2019
DOI: 10.1590/1678-4162-11325
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização microbiológica, físico-química e das condições de produção e comercialização da carne de sol de Salinas, Minas Gerais

Abstract: RESUMO Para avaliar as condições higiênico-sanitárias e tecnológicas (HST) de produção e comercialização da carne de sol no município de Salinas, na região Norte do estado de Minas Gerais, foram coletadas 40 amostras no comércio local para a realização de análises físico-químicas e microbiológicas. A carne de sol é produzida artesanalmente em estabelecimentos comerciais e considerada uma tradição da região. Nas análises físico-químicas de umidade, proteína, gordura, cinzas, cloretos e pH, foram encontrados val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
2
2
0
1
Order By: Relevance
“…The legislation establishes a standard limit of 10³ CFU/g for Staphylococcus aureus, so none of the samples met the acceptable standards for consumption. These results were similar to those obtained by Assis et al (2019), which when performing a microbiological analysis on sun-dried meat, obtained 16 (40%) samples with counts above 10³ CFU/g. Staphylococcus aureus is a microorganism that is part of the natural microbial flora of human beings, being found on the skin, nasal mucous membranes, intestine and respiratory tract.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The legislation establishes a standard limit of 10³ CFU/g for Staphylococcus aureus, so none of the samples met the acceptable standards for consumption. These results were similar to those obtained by Assis et al (2019), which when performing a microbiological analysis on sun-dried meat, obtained 16 (40%) samples with counts above 10³ CFU/g. Staphylococcus aureus is a microorganism that is part of the natural microbial flora of human beings, being found on the skin, nasal mucous membranes, intestine and respiratory tract.…”
Section: Resultssupporting
confidence: 90%
“…The presence of Salmonella in the samples analyzed may be due to inadequate processing practices, related to cross-contamination related to the improper handling of this product, poor storage, and use of inappropriate storage temperature ranges. These results are like those found by Assis et al (2019), which when carrying out the microbiological, physicochemical characterization and the production and marketing conditions of sun-dried meat from Salinas, Minas Gerais, detected the presence of Salmonella spp. in 5% of the samples that were marketed at room temperature.…”
Section: Resultssupporting
confidence: 88%
“…This, in turn, results in a diversity of salt chloride concentrations. Assis, et al [32] state that because the Carne-de-sol is a handcrafted item, there is a wide range of variations in terms of manufacture, physicochemical composition, and microbiological efficacy. The socioeconomic relevance of sun-dried meat in the region is enormous, which justifies the need to better understand its characteristics to assist in the formulation of regional public policies the purpose of which is to ensure the product's sanitary control.…”
Section: Carne-de-solmentioning
confidence: 99%
“…Garcia et al (2013) [43] found for jerked beef a pH of 5.90. Assis et al (2019) [44], reported pH values varying from 5.30 to 6.50 for several samples of commercial sun meat produced in Brazil.…”
Section: Physicochemical Changes During the Dry Salting Kineticsmentioning
confidence: 99%